Financing the inclusive city: the catalytic role of community savings. (April 2018) - Shand, Wayne; Colenbrander, Sarah
Global conversations around financing urban development typically neglect the importance of coordinating the activities of different stakeholders behind a shared vision for their city. In particular, low-income and other marginalized groups must be seen as entrepreneurs and partners in service delivery to enhance the efficacy of resource use and to reduce poverty. This paper explores the creation of non-traditional business models and alliances to invest in informal settlements. It presents examples from India, Kenya, Pakistan, Thailand and Zimbabwe, where local authorities, commercial banks and other formal actors have co-financed and co-delivered urban plans, housing and infrastructure through collaborations with organized groups of the urban poor. These groups make three critical contributions: financial resources, detailed information on the composition of informal settlements, and capabilities for collective decision-making and action. These contributions are underpinned by the financial and social capital developed through collective saving, and enable the delivery of complex urban improvements at scale.